Integrated analysis of the physiological, transcriptomic and metabolomic responses of Neoporphyra haitanensis after exposure to UV-B radiation: an energy metabolism perspective - Wang, Xinyue; Zang, Yu; Xue, Song; Shang, Shuai; Xin, Jiayi; Tang, Liuqing; Chen, Jun; Tang, Xuexi (Frontiers in Marine Science, 2024)
The increase in UV-B radiation at the Earth’s surface due to the depletion of the stratospheric ozone layer is a notable facet of contemporary climate change patterns. The macroalgae inhabiting the intertidal zone exhibit a diverse array of adaptive strategies to cope with dramatic environmental changes. In this study, we integrated physiological, transcriptomic and metabolomic data from energy metabolism perspective to elucidate the responses and recovery mechanism of N. haitanensis to UV-B radiation exposure. UV-B radiation has a harmful impact on the photosynthetic performance of N. haitanensis. However, an increase in photosynthetic performance and upregulated expression of genes related to photosynthesis were observed during recovery, suggesting that the effect of UV-B on N. haitanensis was dynamic photoinhibition. Recovery experiments revealed that most genes and metabolites related to glycolysis were significantly upregulated, suggesting that glycolysis was activated to promote energy production. In addition, the TCA cycle was also activated, as evidenced by the increase in key substances and the upregulated expression of key enzyme-encoding genes during recovery. Correspondingly, ATP was also abundantly accumulated. These results suggested that the TCA cycle provided ATP for N. haitanensis to repair UV-B damage. Meanwhile, amino acid metabolism was enhanced during recovery as a source of intermediates for the TCA cycle. Therefore, photosynthesis, glycolysis, the TCA cycle, and amino acid metabolism synergistically cooperate to provide material and energy for recovery after UV-B radiation. This study is important for understanding the adaptive strategies of intertidal macroalgae in response to UV-B radiation.